The Effect of Inflation and Government Spending on Economic Growth in The West Sumatra Province - Lili Salfina; Nurtati Nurtati; Syofria Meidona; Yully Elvina; dorris yadewani (Husnayain Business Review, 2023)
Indonesia is one of the developing countries facing the problem of economic growth, where one of the factors is inflation and government spending. West Sumatra is one of the provinces in Indonesia that is experiencing economic growth problems. This can be seen from the fluctuating inflation rate and government spending, which can affect the rate of economic growth. This study aims to determine the effect of inflation and government spending on economic growth in West Sumatra Province in 1993- 2020. Methodology/approach – This type of research is quantitative with multiple linear regression analysis using secondary data. Data collection techniques are carried out by collecting and retrieving data through the website of the Central Bureau of Statistics for West Sumatra Province, namely sumbar.bps.go.id. the sample in this study was 28 years old starting from 1993-2020. Findings – It there was a partial and simultaneous effect of inflation and government spending on economic growth in West Sumatra Province from 1993-2020. With the regression results Y = 19.432 - 0.145 X1 – 1.892 X2 and a coefficient of determination of 50.9% means that 50.9% of the independent variables are able to explain the dependent variable, while the remaining 49.1% is explained by other variables not examined in this study. Novelty/value – Inflation is the main factor influencing economic growth in West Sumatra province, while government spending is a supporting factor influencing economic growth in West Sumatra province. To increase economic growth in the province of West Sumatra, the regional government of the province of West Sumatra needs to maintain inflation stability in the form of price stability for goods and services and an increase in appropriate government spending to regulate the course of the economy by determining the amount of government revenue and spending each year which is reflected in regional expenditure revenue budget (APBD) with the aim of stabilizing prices, output levels, employment opportunities and encouraging economic growth in the province of West Sumatra. As employee retention has been an important factor in the Baltic region over the last two decades it is vital to understand how to retain employees.